2022
DOI: 10.3390/jintelligence10030036
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Impacts of Early Musical Abilities on Academic Achievement: A Longitudinal Study

Abstract: Numerous neurological, psychological, and transfer studies confirmed the role of learning music in cognitive development and education. However, exploring the long-term impacts of early musical abilities on academic achievement has gained relatively little attention thus far. In a seven-year longitudinal study, we examined the predictive role of musical abilities in future success in school. The sample consisted of 76 Hungarian students. The independent variables were mothers’ education and the tests administe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 70 publications
0
0
0
2
Order By: Relevance
“…Modern eğitim sistemi içerisinde müzik öğrencilere disiplin ve sorumluluk kazandırarak derslere aktif bir şekilde katılmayı teşvik etmekte (Rusli, 2023), temel ve akademik (Campbell, 2021;Hallam, Creech, & McQueen, 2018;Janurik, & Józsa 2022) becerilerinin geliştirilmesine yardımcı olmaktadır. Akademisyen görüşleri kapsamında araştırma sonucunda yaygın gelişimsel bozuklukları olan öğrencilerin; müzik ve oyun etkinliklerinden çok keyif aldıkları, oyun ve müzik etkinliklerinde kazandıkları bilgi ve becerilerin öğrencileri sonraki hayatlarına hazırladığı, bu etkinliklerin öğrencilerin paylaşma duygusunu tetikleyerek ve beraber etkinlik yapmaya yönlendirerek sosyalleşmelerini sağladığı sonuçlarına ulaşılmıştır.…”
Section: Tartişma Ve Sonuçunclassified
See 1 more Smart Citation
“…Modern eğitim sistemi içerisinde müzik öğrencilere disiplin ve sorumluluk kazandırarak derslere aktif bir şekilde katılmayı teşvik etmekte (Rusli, 2023), temel ve akademik (Campbell, 2021;Hallam, Creech, & McQueen, 2018;Janurik, & Józsa 2022) becerilerinin geliştirilmesine yardımcı olmaktadır. Akademisyen görüşleri kapsamında araştırma sonucunda yaygın gelişimsel bozuklukları olan öğrencilerin; müzik ve oyun etkinliklerinden çok keyif aldıkları, oyun ve müzik etkinliklerinde kazandıkları bilgi ve becerilerin öğrencileri sonraki hayatlarına hazırladığı, bu etkinliklerin öğrencilerin paylaşma duygusunu tetikleyerek ve beraber etkinlik yapmaya yönlendirerek sosyalleşmelerini sağladığı sonuçlarına ulaşılmıştır.…”
Section: Tartişma Ve Sonuçunclassified
“…Eğitimin her boyutunda yer alan öğrenme alanlarından biri olan müzik eğitimi, normal gelişim gösteren çocuklar kadar yaygın gelişimsel bozukluğu olan ve özel eğitim gereksinimi olan çocukların eğitimini destekleyen nitelikler barındırmakta ve kişilik gelişiminde önemli bir yer tutmaktadır (ÖEHY, 2018). Müzik eğitimi aynı zamanda yeni bilgiler ve kavramların öğretilmesine (Archontopoulou & Vaiouli 2020;Lee & Lin, 2023;Campbell, 2021;Çadır, 2008;Hallam, Creech, & McQueen, 2018;Janurik, & Józsa 2022;Önal, 2010;Eren, Deniz & Düzkantar, 2013;Ünal, Ece & Yıkmış, 2016;Yıkmış, Terzioğlu, Kot & Aktaş, 2017Yılma & Uçan, 2014), çocuğun çevresi ile ilişki kurarak sosyalleşmesine (Kern, Woley & Aldridge, 2006;Kossyvaki, 2020;Saldana, 2016;Yılmaz, Topaloğlu, & Akyüzlüer, 2014;Yoon, 2021), problem davranışlarının azaltılmasına (Gökmen, 2010;Yükselsin & Berrakçay, 2010), psikomotor becerilerin artırılmasına (Nacakçı & Dalkıran, 2016;Kara, 2019)…”
unclassified
“…To further investigate how these experiences affect students, Márta Janurik and Kriaztián Józsa (2022) analyzed academic abilities, musical aptitude, and intelligence of students engaged in after-school music programs. They found that musical abilities were associated with cognitive benefits that proved to be key predictors of GPA (Janurik, 2022). This is because the development of music abilities is a complex activity that requires persistence, decoding of patterns, motor coordination, and familiarization with musical structures (Janurik, 2022).…”
Section: Collaboration In Music Coursesmentioning
confidence: 99%
“…They found that musical abilities were associated with cognitive benefits that proved to be key predictors of GPA (Janurik, 2022). This is because the development of music abilities is a complex activity that requires persistence, decoding of patterns, motor coordination, and familiarization with musical structures (Janurik, 2022). The nature of learning a new skill in a collaborative environment allows students to have increased cognitive benefits such as persistence and motivation that allow for increased AcaAchieve.…”
Section: Collaboration In Music Coursesmentioning
confidence: 99%
See 1 more Smart Citation